Secularism, Nationalism, and Minorities in Turkey - Merǆanova, Ina (Journal of religion in Europe, 2014)
The vivid interest in the philosophical and legal premises of secularism in Turkey, as well as in its workings in the public and private life of Turkish citizens resonates with an ongoing questioning in Western academia of the validity of established theories of secularization. More importantly, the political and social transformations in Turkey itself, and the growing role and visibility of Islam in the public sphere, especially during the last decade marked by the rule of the Islamic-oriented Justice and Development Party (jdp), have triggered a search for new explanatory frameworks and reconceptualization of Turkish secularism.The four books discussed in this article tackle the interrelated issues of secularism, nationalism and minorities in Turkey from a variety of disciplinary and methodological perspectives.